Numerical Study of Erosion Wear on Centrifugal Slurry Pump - Sharma, Abhineet Kumar (My University, 2008)
Slurry erosion is a crucial problem in many industrial applications, due to impingement of solid particles being suspended in the fluids flowing at high velocity. It affects both the initial cost and life of the component. Erosive wear can be found on impellers & volute casing in slurry pumps, angled pipe bends, turbines, pipes and pipe fitting, nozzles, burners etc. The volume loss due to erosion is a troublesome problem for slurry transportation. The service life of equipments handling solid–liquid mixture can be increased by reducing the erosion wear. It is therefore necessary to study erosion wear systematically, so that efforts can be made to minimize the wear during design stage. Centrifugal pumps are generally used for slurry transport. Due to erosion, the life of pumps used is very short and they need to replace periodically. In the present work a systematic study on the erosion wear has been carried out to improve the present understanding .Numerical simulation has been carried out for radial flow impeller and the effect of affecting parameters on erosion wear has been studied .The results clearly indicated that all factors contribute to wear of centrifugal pump impeller. The erosion rate of blades is 10 times greater than the erosion wear of hub. The erosion rate is found to be more severe near the leading edge as compared to other parts of impeller. The simulations which were carried out on impeller show that particle size affects the erosion rate only up to certain size of particles and depends on the impact angle.
Keywords: Centrifugal slurry pump, erosion wear,speed.